Phytochemical profiling and anticancer potential of pistachio wastes against MCF-7 breast cancer cells: a metabolic and apoptotic pathway analysis - Levent Gülüm; Emrah Güler; Çağla Başak Zırhlı; Ayşe Büşranur Çelik; Yusuf Tutar (BMC Complementary Medicine and Therapies)
Abstract Food waste poses significant environmental, economic, and social challenges worldwide. Pistachio waste is recognized for its health benefits, particularly for its anticancer properties. This study assessed the phytochemical characteristics of pistachio hull (PH) and shell (PS) using various solvents (ethyl acetate, hexane, and methanol). Methanolic extracts showed substantially higher phenolic and flavonoid contents along with enhanced antioxidant activity across all tested methods, with PH consistently outperforming PS in antioxidant properties. Cell viability tests on MCF-7 cancer cells indicated that PH-Hexane had a slightly greater effect than PH-ethyl acetate and PH-methanol. Cell cycle analysis revealed a notable arrest in the G0/G1 phase compared to the control group. Additionally, PH-Hexane treatment resulted in 21.24% apoptosis, primarily early apoptosis at 19.41%. The pathway analysis involving 46 genes revealed that PH-Hexane induces apoptosis in MCF-7 cancer cells by modulating several metabolic pathways, particularly those associated with the immune system, developmental biology, signal transduction, and cellular responses to stimuli. This induction was characterized by the substantial upregulation of the CEBPB, HIF1A, and MYC genes and the significant downregulation of ATF2, CEBPA, and NR3C1 genes. The findings of this study indicate that the hexane extract derived from high-oil-content wastes has potential as an anticancer agent. Future research on oil-rich plant-based wastes should consider utilizing hexane as a solvent for further exploration of anticancer properties.